Distribution of CBCT-3D examination referrals at Dental Hospital Universitas Airlangga - Eha Renwi Astuti; Deny Saputra; Aga Satria Nurrachman; Dina Karimah Putri; Ratu Sofia Nur Aini; Umi Lutfiah (Ikatan Radiologi Kedokteran Gigi Indonesia, 2021)
Objectives: This study aims to find out the distribution of CBCT-3D examination referrals at Dental Hospital Universitas Airlangga based on the origin of referral, specialist field, age and gender. Materials and Methods: This descriptive research is using the total sampling method. Secondary data from the medical records of any referral patients for CBCT-3D examination at Dental Hospital Universitas Airlangga from July 2015 to March 2020 were included in this study. Furthermore, data references were tabulated and presented in the form of a pie chart. Results: The distribution of CBCT-3D examination referrals at Dental Hospital Universitas Airlangga was as high as 323 (77.64%) coming from within the hospital and as much as 93 (22.36%) from outside of the hospital. Based on the dental specialties who made the referral, six of seven departments have referred their patients for CBCT examination with varying proportions and indications. The distribution of referrals was also divided into gender (male or female) and several age categories based on the Indonesian Ministry of Health, such as toddlers (ages 0-5 years), children (ages 5-11 years), adolescents (ages 12-25 years), adults (ages 26-45 years), elderly (ages 46-65 years) and seniors (over 65 years). Conclusion: Referrals for CBCT-3D radiography examinations at Dental Hospital Universitas Airlangga are mostly from within the hospital, from the Department of Oral and Maxillofacial Surgery. Female patients and the elderly (46 years and older) were found to be the most frequently referred.